Distributed Drives Monitoring and Control: A Laboratory Setup - Mini Sreejeth; Parmod Kumar; Madhusudan Singh (Journal of Engineering)
A laboratory setup of distributed drives system comprising a three-phase induction motor (IM) drive and a permanent magnet synchronous motor (PMSM) drive is modeled, designed, and developed for the monitoring and control of the individual drives. The integrated operation of IM and PMSM drives system has been analyzed under different operating conditions, and their performance has been monitored through supervisory control and data acquisition (SCADA) system. The necessary SCADA graphical user interface (GUI) has also been created for the display of drive parameters. The performances of IM and PMSM under parametric variations are predicted through sensitivity analysis. An integrated operation of the drives is demonstrated through experimental and simulation results.